2017
DOI: 10.1039/c6ra25912j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of mesostructured cellular foam silica supported Cu–Ce mixed oxide catalysts for CO oxidation

Abstract: A series of mesostructured cellular foam (MCF) silica supported CuO–CeO2 catalysts with various total metal loadings (10–40 wt%) and various Cu/Ce ratios (Cu/Ce = 1/9, 2/8, and 3/7 wt/wt) were prepared and tested for CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…[7][8][9] In particular, much attention has been paid to copper-doped ceria-based catalysts because of their unique activity for ambient CO oxidation. [10][11][12][13][14] It should be noted that synergistic redox properties are produced upon the formation of CuO-CeO 2 interfacial sites, which are considered to be the active sites for the CO oxidation reaction. 15 Moreover, the substitution of Ce 4+ cations with Cu 2+ promotes the formation of structural defects and oxygen vacancies on the catalyst surface, which can favor the generation and mobility of charged species, such as electrons or oxygen anions in the solid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In particular, much attention has been paid to copper-doped ceria-based catalysts because of their unique activity for ambient CO oxidation. [10][11][12][13][14] It should be noted that synergistic redox properties are produced upon the formation of CuO-CeO 2 interfacial sites, which are considered to be the active sites for the CO oxidation reaction. 15 Moreover, the substitution of Ce 4+ cations with Cu 2+ promotes the formation of structural defects and oxygen vacancies on the catalyst surface, which can favor the generation and mobility of charged species, such as electrons or oxygen anions in the solid catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…7 that there is a sharp peak at a binding energy of 932.2 eV, which is the characteristic peak of cuprous oxide. 19,20 Clearly, this conrms that the main component (in addition to carbon) of the friction lm was cuprous oxide in the proposed process of wear. [21][22][23] The C/O and C/Cu contents in the RECMs without SGO are signicantly lower than those of the RECMs with SGO ( Table 2).…”
Section: Xps Analysis Of Wear Surfacementioning
confidence: 94%
“…Moreover, it should be noted that the Ce-loading on our CeO x^C uO-EE samples was quite lower than that on reported Ce-Cu-contained composite catalysts, 21,[27][28][29]34,[37][38][39][40][41] for comparison, the detailed information of some typical samples was collected in Table 2. It can be found that although the Ce loading or Ce:Cu atomic ratio on our CeO x^C uO-EE samples was not more than one tenth of that on most reported Ce-Cu composited catalysts, the comparable or higher surface concentrations of Ce(III), Cu(I) and Os were obtained on our samples.…”
Section: -7mentioning
confidence: 99%
“…These results clearly indicated that CeO x^C uO-EE samples with Ce-embedded interactive surface were more competitive to achieve superior heterogeneous catalysis performance in comparison with conventional CeO x / CuO-kind samples. The factor being responsible for the superior activity of CeO x^C uO-EE samples could be mainly attributed to the Ce(IV)-Ce(III) and Cu(II)-Cu(I) co-present Ce-O-Cu interactive surface constructed from chemically embedding of Ce into the surface of Cu-based substrate, since the synergistic e®ect present by the transformation of CeðIVÞ þ CuðIÞ $ CeðIIIÞ þ CuðIIÞ during the catalytic cycle has been recognized the main factor to in°uence the surface chemical properties of Ce-O-Cu composited structures such as the acidic feature, the reactivity with reactants and the mobility of active oxygen species, 22,28,[37][38][39][40][41] in turn, these properties would greatly impact on reaction behaviors and govern catalytic performance. 16,45,46 In our case, by modulating and controlling the Ce dosage at 1.6 wt.% for preparing CeO x^C uO-EE structure, the comprehensive surface properties could be manipulated to the optimal level among samples (as disclosed in Table 1), which could be the clue to understand the superior catalytic performance of CeO x (1.6 wt.%)^CuO-EE.…”
Section: Tof ¼ ðPv =Rt þX Nmentioning
confidence: 99%
See 1 more Smart Citation